Thermal conductivity and mechanical properties of nitrogenated holey graphene - Mortazavi, Bohayra; Rahaman, Obaidur; Rabczuk, Timon; Pereira, Luiz Felipe C. (Carbon (New York), 2016)
Nitrogenated holey graphene (NHG), a two-dimensional graphene-derived material with a C2N stoichiometry and evenly distributed holes and nitrogen atoms in its basal plane, has recently been synthesized. We performed first principles calculations and molecular dynamics simulations to investigate mechanical and heat transport properties of this novel two-dimensional material at various temperatures. First principles calculations based on density functional theory yield an elastic modulus of 400 ± 5 GPa at 0 K, 10% larger than predicted by molecular dynamics simulations at low temperatures. We observed an overall decreasing trend in elastic modulus and tensile strength as temperature increases. At room temperature, we found that NHG can present a remarkable elastic modulus of 335 ± 5 GPa and tensile strength of 60 GPa. We also investigated the thermal conductivity of NHG via non-equilibrium molecular dynamics simulations. At 300 K an intrinsic thermal conductivity of 64.8 W/m-K was found, with an effective phonon mean free path of 34.0 nm, both of which are smaller than respective values for graphene, and decrease with temperature. Our modeling-based predictions should serve as guide to experiments concerning physical properties of this novel material.